(untitled) (UNED Research Journal, 2019)
Introduction: Current research of fish locomotion is focused on creating better underwater vehicles and how environmental stress factors modify swimming. Objective: To study the relation of morphometric characteristics with burst swimming in six representative species of continental fishes from Costa Rica. Methods: We measured total length, standard length, height and area of the tail of 38 individuals from six species. We used a Kruskall-Wallis test and a Boxplot graphic to compare species; and a PCA test to identify body variables that influence swimming. A Non-Metric Dimensional Scaling (NMDS) test was done for species and position in the water column. Results: The fastest swimming corresponded to A. nigrofasciata (9,29cm/s), while S. salvini (1,65cm/s) was the slowest. Burst swimming speed is influenced by body size and tail type, and differed with position in the water column, being surface species the fastest. Conclusions: Morphological and ecological characteristics determine differences in burst swim.